Emerging armchair travel: investigation of authentic armchair travel experiences and their effect on armchair travel stickiness - Chua, Bee-Lia; Kim, Seongseop (Sam); Hailu, Tadesse Bekele; Yu, Jongsik; Moon, Hyoungeun; Han, Heesup (Informa UK Limited, 2023)
Armchair travel is a kind of tourism that gives a vicarious travel experience. This study aimed to examine the influence of authentic travel experiences on travel stickiness using the framework of stimulus-organism-response. Our result revealed that flow and functional experiences positively affected authentic travel experiences with armchair travel. Furthermore, authentic travel experiences positively influenced value and engagement. Customer engagement influenced customer stickiness to armchair travel, while overall value did not. This study provides insightful theoretical implications for the extant armchair travel literature and practical implications for developing new tourism products or programs to keep pace with rapidly shifting industry trends.